2007
DOI: 10.1111/j.1471-6712.2007.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of violence and its relation to caregivers’ demographics and emotional reactions – an explorative study of caregivers working in group homes for persons with learning disabilities

Abstract: The aim of the study was to investigate the prevalence of violence directed towards caregivers working in group homes for persons with learning disabilities, and to examine the relation between violent incidents and caregivers' demographics such as gender, age, years in service, years at the present workplace and education, as well as emotional reactions to violence expressed by the caregivers. A questionnaire was distributed to all caregivers, i.e. Registered Nurses, assistant nurses and nurse's aides, workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
9

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 39 publications
1
32
1
9
Order By: Relevance
“…age, experience in nursing, gender, personality traits) to their level of experienced workplace violence 2,20,22,29,31 . This study reported here did not measure the personality traits of nurses, and analysis of the demographic data of the participants did not find any significant association between gender, age of the nurse, experience of the nurse and their reports of workplace violence 24,31,33 . Findings on the job level of nurses were inconsistent between the sectors, with no difference in experience of workplace violence and level of nurse in the public sector.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…age, experience in nursing, gender, personality traits) to their level of experienced workplace violence 2,20,22,29,31 . This study reported here did not measure the personality traits of nurses, and analysis of the demographic data of the participants did not find any significant association between gender, age of the nurse, experience of the nurse and their reports of workplace violence 24,31,33 . Findings on the job level of nurses were inconsistent between the sectors, with no difference in experience of workplace violence and level of nurse in the public sector.…”
Section: Discussionmentioning
confidence: 53%
“…Although there has been a focus on organizational initiatives, there is also a large body of work that links the individual characteristics of nurses (e.g. age, experience in nursing, gender, personality traits) to their level of experienced workplace violence 2,20,22,29,31 . This study reported here did not measure the personality traits of nurses, and analysis of the demographic data of the participants did not find any significant association between gender, age of the nurse, experience of the nurse and their reports of workplace violence 24,31,33 .…”
Section: Discussionmentioning
confidence: 65%
“…These findings for workshops are comparable to those for residential homes. The percentage of those who experienced violence during their work in residential homes varies between around one third and 80% [24,25]. …”
Section: Discussionmentioning
confidence: 99%
“…Based on a survey conducted by the Institute of Hospital Management of China, 73.3% of the 270 investigated Chinese hospitals experienced various kinds of workplace violence [10]. Not only does the workplace violence in hospitals affect the health of medical workers [11][12][13], but also the quality of health services -through negatively influencing the morale and self-confidence of health care staff [14,15]. Moreover, workplace violence can lead to a decline in work efficiency and job satisfaction [11], higher turnover intention, and eventually brain drain [16,17], which in turn bring about a negative effect on work-related attitudes.…”
Section: Frequency Of Experiencing or Witnessing Workplace Violencementioning
confidence: 99%